P09.34 Molecular identification of treponema pallidum strains from syphilitic lesions in sti clinic patients, lima, peru. (13th September 2015) - Flores, JA; Vargas, SK; Leon, SR; Konda, KA; Chow, JY; Calvo, GM; Salvatierra, HJ; Brown, B; Klausner, JD; Caceres, CF
Abstract : Background: In Peru, syphilis disproportionally affects men who have sex with men (MSM) and male-to-female transgender women (TW) with prevalence rates as high as 21%. To our knowledge, there are no available data describing circulating strains of T. pallidum in Lima, Peru. We used the CDC subtyping scheme to identify T. pallidum circulating subtypes among MSM and TW from two STI clinics in Lima, Peru. Methods: A cohort of 401 MSM and TW were assessed for syphilis infection at baseline and quarterly with RPR (BD Macro-Vue, USA) and TPPA (Fujirebio, Japan) testing up to 24 months. A dacron swab was used to collect exudate from chancre-like lesions and placed into 500 µL of lysis buffer. DNA extraction was performed using QIAamp mini kit (Qiagen, Valencia, CA). Using specific primers for Tp47 region target, an aliquot of the DNA sample was amplified using conventional PCR. Subtyping of T. pallidum TP47 positives was performed using detection of number of 60-bp tandem repeats in the arp gene and analysis by RFLP of 3 tpr genes (TprE, G, J) according to CDC guidelines. Results: Among 401 participants, 26 presented with primary syphilitic lesions at baseline or follow-up with RPR (TPPA confirmed) titers ranging from 1:2–1:64. Of those 26 total lesions, 1 (7%) of 14 tested was dark-field positive. TP DNA screening using TP47 PCR yielded 12 (44.4%) positives. Among eight typable, four were subypes 14d (33.3%), two 15d (16.7%), one 16d (8.3%) and one 0d (16.7%) where 0 = non-typable arp. Conclusion: T. pallidum subtypes 14d and 15d were the most prevalent strains in lesions obtained from MSM/TW who had chancre-like lesions in Lima, Peru. Dark field testing results and typing difficulties could be due to low bacterial load and needs to be considered in sampling methods. Disclosure of interest statement: The study Picasso is funded by a NIAID grant and was implemented by Cayetano Heredia in collaboration with the University of California Los Ángeles. The molecular part of the study was implemented under the supervision of the University of Washington. No pharmaceutical grants were received during the development of this study.